Guidance and Control Technology of Spacecraft on Elliptical Orbit - Liu, Fucheng; Lu, Shan; Sun, Yue (Navigation: Science and Technology, 2019)
This book introduces readers to the navigation, guidance and control technologies involved in single-spacecraft, double-spacecraft, and multiple-spacecraft tasks in elliptical orbits. It comprehensively covers the key technologies of guidance, navigation and control (GNC) system design for spacecraft in elliptical orbits, including the orbit design, formation configuration design and maintenance, autonomous navigation technology and relative navigation technology, as well as autonomous rendezvous technology. The methods that this book introduces are very close to actual practical engineering applications and presented in an accessible style. The book can serve as reference teaching material for senior undergraduates and postgraduates with space navigation related majors, while also providing essential information and guidance for research personnel and engineering technical personnel engaged in the development of GNC systems for spacecraft.